Oriented Chiral DNA–Silica Film Guided by a Natural Mica Substrate. (6th January 2016) - Cao, Yuanyuan; Kao, Kunche; Mou, Chungyuan; Han, Lu; Che, Shunai
Abstract: The formation of highly ordered chiral organic/inorganic films with high density and long‐range orientation is important in constructing chiral devices, such as broadband polarization devices, liquid‐crystal displays, or negative‐reflection materials. A feasible strategy is presented to fabricate three‐dimensional mesostructured chiral DNA–silica assemblies into large‐scale oriented arrangements. The highly ordered film was aligned by a mica crystal substrate with the bridging effect of suitable divalent metal ions, followed by the growth of the DNA–silica composite by bottom‐up assembly with a "quartet templating" method. This simple and effective route would perform well in the alignment and arrangement of highly charged biomolecules, such as polypeptides, proteins, viruses, and their inorganic assemblies, and furthermore could allow the fabrication of chiral optical materials with long‐range ordering.